Boruto : Naruto next generations. Volume 11, The new team seven - Kodachi, Ukyo, 1979-; Kishimoto, Masashi, 1974- (Shonen Jump manga., 2021)
"The ninja adventures continue with Naruto's son, Boruto! Naruto was a young shinobi with an incorrigible knack for mischief. He achieved his dream to become the greatest ninja in his village, and now his face sits atop the Hokage monument. But this is not his story... On a mission to rescue the imprisoned Naruto, Boruto and his teammates find themselves up against the dastardly Boro. This new team will need to learn to work together quickly to have any hope of surviving"--